Perceived stress and coping strategies during the COVID-19 lockdown in five countries - Bedoya Cardona, Erika Yohanna; Pereira Moreno, Lady Johanna; Popa, Ioana; Morandi, Anna; Molina-Fernández, Antonio; Hansen-Rodríguez, Gisela; Filgueiras, Alberto; Hernández Montaño, Alicia; González Tovar, José; Vilagrá Ruiz, Raul; Pinto Marques, Mauricio; Bueno Castellanos, Claudia; et al. (Revista de psicopatología y psicología clínica, 2023)
Several studies have shown how mental health could be affected during the COVID-19 pandemic, which led us to wonder about the psychological impact that the initial period of lockdown could have. We conducted a multicentric study that sought to describe, compare, and analyze the association between perceived stress, coping strategies and sociodemographic characteristics in a snowball-style convenience sample of 1169 participants from Colombia, Brazil, Mexico, Italy, and Spain who responded to an online survey. There were differences in perceived stress and coping strategies between countries and depending on sociodemographic characteristics. The variables positively associated with perceived stress were the coping strategies alcohol-drug use, focus on emotions and venting, being a woman, and living in Brazil, Italy, and Spain. The variables negatively associated with perceived stress were planning and active coping, positive reinterpretation, being over 45 years old, and being a worker. These results contribute to understanding the stress responses to lockdown and help identify vulnerability factors in order to design prevention and intervention programs. Keywords: Perceived stress; coping strategies; COVID-19; lockdown; pandemic.